Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.31488/ejrm.132
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Nebulised Anti-Inflammatory Solution of Alkaline Hypertonic Ibuprofen (AHI) for Treatment of SARS-Cov-2 Infection: A Compassionate Study with a Comparator Arms

Abstract: Background. This retrospective study evaluates the efficacy of inhalation therapy with alkaline hypertonic ibuprofen (AHI) in COVID-19 positive patients compared to a control group of patients who received conventional treatment. The study was carried out at the Orías Hospital in Jujuy Province, Argentina, from June to September 2020, with final follow-up on September 30. Methods. The study included 99 COVID-19 positive patients with moderate to severe disease (respiratory distress and/or hypoxemia). The contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…5 Three retrospective observational studies have been carried out in Argentina with NaIHS in moderate and severe COVID-19 pneumonia. The first study analysed data from 99 patients 3 and the second study analysed data from 383 patients (15% mechanically ventilated), 4 both showing similar preliminary results: a significant reduction in mortality, improvement of clinical outcomes, rapid reversal of hypoxaemia and decrease in hospitalization stay in pneumonia and COVID-19-associated acute respiratory distress syndrome (CARDS). 3,4 The third and most relevant study, conducted with the approval of the Institutional Review Board of the National Bureau of Economic Research of Harvard and Columbia Universities, 5 analysed data from 5146 patients 5 and concluded that NaIHS reduces mortality by 48.7%.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…5 Three retrospective observational studies have been carried out in Argentina with NaIHS in moderate and severe COVID-19 pneumonia. The first study analysed data from 99 patients 3 and the second study analysed data from 383 patients (15% mechanically ventilated), 4 both showing similar preliminary results: a significant reduction in mortality, improvement of clinical outcomes, rapid reversal of hypoxaemia and decrease in hospitalization stay in pneumonia and COVID-19-associated acute respiratory distress syndrome (CARDS). 3,4 The third and most relevant study, conducted with the approval of the Institutional Review Board of the National Bureau of Economic Research of Harvard and Columbia Universities, 5 analysed data from 5146 patients 5 and concluded that NaIHS reduces mortality by 48.7%.…”
Section: Introductionmentioning
confidence: 98%
“…1 As previously exposed, NaIHS has been used in moderate and severe COVID-19 pneumonia, in the modality of compassionate use and covered by the Declaration of Helsinki. [3][4][5] Accordingly, it was approved for emergency use in several Argentine provinces and its phase II clinical trial (Pegasus trial) was approved in July 2021, by the Drug, Food and Technology National Administration of Argentina. 5 Three retrospective observational studies have been carried out in Argentina with NaIHS in moderate and severe COVID-19 pneumonia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are available three observational studies in the compassionate use modality in moderate and severe Coronavirus Disease 2019 (COVID-19) pneumonia, carried out in Argentina, [1][2][3] with all three studies concluding that there was a significant reduction in mortality. [1][2][3] The most recent of these was conducted with the approval of the Institutional Review Board of the National Bureau of Economic Research (NBER) of Harvard and Columbia Universities, which analysed data from 5146 patients and concluded that NaIHS reduced mortality by 48.7%, 3 although randomized clinical trials are steel needed to confirm these data.…”
mentioning
confidence: 99%